Bis(trifluoromethylsulfonyl)imide‐based frozen ionic liquid for the hollow‐fiber solid‐phase microextraction of dichlorodiphenyltrichloroethane and its main metabolites. Issue 16 (10th July 2017) - Pang, Long; Yang, Peijie; Pang, Rong; Li, Shunyi
Abstract : 1‐Hexadecyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide is a solid‐phase ionic organic material under ambient temperature and is considered as a kind of "frozen" ionic liquid. Because of their solid‐state and ultra‐hydrophobicity, "frozen" ionic liquids are able to be confined in the pores of hollow fiber, based on which a simple method was developed for the hollow‐fiber solid‐phase microextraction of dichlorodiphenyltrichloroethane and its main metabolites. Under optimized conditions, the proposed method results in good linearity ( R 2 > 0.9965) over the range of 0.5−50 μg/L, with low limits of detection and quantification in the range of 0.33−0.38 and 1.00−1.25 μg/L, respectively. Intra‐ and interday precisions evaluated by relative standard deviation were 3−6 and 1−6%, respectively. The spiked recoveries of dichlorodiphenyltrichloroethane and its main metabolites from real water samples were in the range of 64−113 and 79−112%, respectively, at two different concentration levels. The results suggest that "frozen" ionic liquids are promising for use as a class of novel sorbents.